Preliminary analysis of quality of life (QOL) before and after surgery for female genital fistula. A prospective cohort study - Saha, Stacy; Ambauen-Berger, Bea; Munira, Shirajum (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe the characteristics of women who come for repair of FGF, assess their QOL before & after surgery and estimate factors associated with improved quality of life. Methods: All women who came to LAMB for FGF repairin 2016 and 2017 were interviewed on admission and called for a follow-up visit 6 months after successful surgery. Sociodemographic, obstetric, and fistula-related information was collected on admission. Health related QOLwasmeasured using the 36-item short form (SF-36), and perception of stigma and discrimination were assessed on admission and at follow-up. Results: A total of 72 women were included.Mean age was 40.1 years, 49% had no education, and 42% were in the poorest wealth quintile.The mean stigma score (out of 7)went from 3.79 to 1.40 post surgery (p<0.001) and the mean discrimination score (out of 5)went from 2.2 to 0.4 (p<0.001). The mean score for all eight of the general health categories increased significantly after surgery (p<0.01 to 0.001). Poor women started lower but showed evidence of greater improvement in health related QOL compared to richer women (p<0.05)) and some evidence of greater improvement in discrimination (p<0.1). Women with no education had a larger decreasein perceived stigma (p= 0.03) compared to the educated. Conclusions: Surgery for FGF improves quality of life, with poor women showing greater increase in health related QOL and uneducated women reporting a greater decrease in stigma. Further multivariable analysis is needed to determine which factors remain associated with improved QOL.